Urine protein quantification in stacking gel by SDS‐PAGE. Issue 4 (26th November 2018) - Jia, Jia; Pan, Jie; Xu, Hongpan; Wang, Sen; Bai, Bing
Abstract: Urine total protein concentration is usually measured by the pyrogallol red‐molybdate (PRM) assay in clinical laboratories, but it is often subject to sample interference. Here, we introduce a stacking gel‐based method for accurate protein quantitation. In this method, the urine protein samples are run into the stacking gel by SDS‐PAGE where it is concentrated into a single band, and then quickly stained by 0.001% Coomassie at high temperature. High correlations were found between the BSA and urine protein standards ( R 2 = 0.997 and 0.990, respectively). Addition of 80 ng urine protein standard into each of the ten clinical urine specimens with questionable PRM results yielded the expected increase in the results by this method. Comparison of the PRM method and with the gel quantitation approach on about 60 clinical urine samples demonstrated a general consistency between the results ( R 2 = 0.825), but in PRM samples with lower protein concentration showed more variations. Overall, the stacking gel method might be a good alternative for clinical urine samples with suspicious protein concentration results.